Estudo da influência do contexto esportivo no status de identidade de atletas de futebol de campo - Vissoci, João Ricardo Nickenig (2009)
The main objective of this study was to investigate de influence of soccer's context in athletes' identity in different sport career phases. Participated in the study 120 male soccer athletes born from the year of nineteen hundred and ninety to nineteen hundred and ninety five, whom practice soccer in formation schools linked to a soccer club from the first division of the Brazilian soccer championship, from the state of Paraná. As for data collection the following instruments were used: The sport motivation scale, Athletic coping skills scale-28, a rearing perception scale and a semi-structured interview. Data collection was performed in the sports schools in sessions scheduled by the coaches. Quantitative data analysis was determined through variance homogeneity evaluation test Levene to determine the statistical treatment, which was performed through Kruskal- Wallis test with Mann-Whitney post hoc, ANOVA one way, with Bonferroni post hoc, ANOVA repeated measures and the Cronbach's alpha coefficient. The qualitative data were analyzed through content analysis of categorical type. The results evidenced higher levels of self-determination, higher coping strategies variability and higher perception of parent support through the sport career development. Transitions in the athletic domain showed a preference for soccer in relation to other activities. Specialization athletes were already treated like professionals and evidenced a sport career with future perspectives and financial growth. In the investment phase the dedication to soccer practice was exclusive, the athletes were professionalized and participated in national and international. At psychological domain soccer was performed as a meaningful and important activity to the country, the athletes showed better judgment with the continuity in sport's context and role satisfaction promoting social featuring in spite of the perception of the effort necessary to reach high performance. At social level the family remained as the main support element to the athletes in all the athletic development phases. It was evidences that the athletes had difficulties coping with family distance and to establish interpersonal relationships in and out of the club, restricting, in the investment phase, the focus of friendship to people inside de club. At academic level the athletes showed difficulties in maintaining a student/athlete life but studies were seen as an alternative to the athletes' career. Sport environment was characterized as restricted in relation to activities performed through the sport career. Interpersonal relationships focus was directed to the sport context with the career development. The roles one adopted were varied in the experimentation phase and diminished and got restricted to the athletes' role in the investment phase. Two types of identity statuses were observed, execution and identity achievement. The athletes at execution status showed less selfdetermination (extrinsically motivated), with less variability of coping strategies and perception of support and high protections by parents rearing. Achievement athletes demonstrated high self-determination, with several coping strategies and with perception of support from parents during rearing. So it is concluded: context characteristics may influence in athletes' development restricting ones experience, interpersonal relationships and role adoption hardening the development in other domains, possibly influencing athletes' identity statuses and life cycle continuity.